Human adaptation in the 7th-11th century - Szathmáry, László; Guba, Zsuzsanna (Acta Biologica Szegediensis, 2002)
This paper is an attempt to reconstruct human adaptability in the case of populations which lived in the central region of the Carpathian Basin between the 7th and 11th century. On drawing a parallel between the ecological zonality and the human anatomical patterns of the three historical periods included, we come to a conclusion that the populations of both the Late Avar period (670-894 A.D.) and the time of the Hungarian conquest (10th century, i.e. 895-999 A.D.) adapted themselves to the local ecological zonality fairly well, while, from 1000 A.D. on, i.e. at the time of the 11th century when the early Christian Hungarian Kingdom was founded by King St. Stephen, it may have been political intention more than anything else that influenced the structure of population.